Who will provide security for the Arctic? - O. V. Aleksandrov (Vestnik MGIMO-Universiteta)
This article is devoted to a problem of security of the Arctic region. The author portrays the contemporary state of the Arctic region, indicates changes which happened in the region after the end of "the cold war", analyzes the role which regional and non-regional institutions can play in the security protection of the Arctic, and also focuses attention on the Russian approach to a problem of security of the Arctic.